Glassy crystals of adamantane derivatives induced by thermal treatment - Szewczyk, D.; Jeżowski, A. (Хабаршы. Физика сериясы, 2015)
Observing a first-order transition between the supercooled liquid state and a new amorphous phase, the “glacial state” has been one of the most interesting focus during the last decades. At present the glacial state is seen as an interrupted crystallization due to the low crystal growth rate from the glass state. In this work, we will describe the first glacial state obtained from a plastic crystal for two materials - adamantane derivatives.